Therapeutic Potential of Triptolide as an Anti-Inflammatory Agent in Dextran Sulfate Sodium-Induced Murine Experimental Colitis - Tang, Bufu; Zhu, Jinyu; Zhang, Baohui; Wu, Fazong; Wang, Yajie; Weng, Qiaoyou; Fang, Shiji; Zheng, Liyun; Yang, Yang; Qiu, Rongfang; Chen, Minjiang; Xu, Min; et al. (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn's disease (CD), is a group of chronic and incurable inflammatory diseases involving the gastrointestinal tract. In this study, we investigated the anti-inflammatory effects of triptolide in a dextran sulfate sodium (DSS)-induced mouse colitis model and LPS-activated macrophages and explored the specific molecular mechanism(s). In mice, triptolide treatment showed significant relief and protection against colitis, and it markedly reduced the inflammatory responses of human monocytes and mouse macrophages. Pharmacological analysis and weighted gene co-expression network analysis (WGCNA) suggested that PDE4B may be an important potential targeting molecule for IBD. Exploration of the specific mechanism of action indicated that triptolide reduced the production of ROS, inhibited macrophage infiltration and M1-type polarization by activating the NRF2/HO-1 signaling pathway, and inhibited the PDE4B/AKT/NF-κB signaling cascade, which may help weaken the intestinal inflammatory response. Our findings laid a theoretical foundation for triptolide as a treatment for IBD and revealed PDE4B as a target molecule, thus providing new ideas for the treatment of IBD.